2021
DOI: 10.3390/ani11082213
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Dried Plasma Improves Body Weight, Intestinal Barrier Function, and Tibia Strength during Experimental Constant Heat Stress Conditions

Abstract: The aim of this study was to see how spray-dried plasma (SDP) supplementation affected broiler chicken performance, intestinal permeability, and bone strength during persistent heat stress. One-day-old chicks (n = 480) were randomly assigned into twelve environmental corrals; four thermoneutral (TN-negative control, maintained at 24 °C from d 21–42); four heat stress (HS, exposed to 35 °C from d 21–42); and four heat stress treated with 2% SDP in the feed until d 28 followed by 1% SDP until d 42 (HS-SDP). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The results of the IgA concentration analysis in the intestinal and tracheal washes at 21 and 42 days of age indicate that the inclusion of SDP in the preliminary diet increased the titer of this immunoglobulin isotype, just the opposite effect to that observed with the inclusion of mycotoxins in feed that decreased IgA titers in both intestine and trachea. This information is important given that IgA is the isotype of immunoglobulin found in the mucosa, protecting at this level against antigens and toxins (54), and suggests that chicks receiving SDP in the diet have a greater immune capacity, as well as probably a stronger integrity of the gut barrier, as observed when chicks are subjected to systemic inflammation (55).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the IgA concentration analysis in the intestinal and tracheal washes at 21 and 42 days of age indicate that the inclusion of SDP in the preliminary diet increased the titer of this immunoglobulin isotype, just the opposite effect to that observed with the inclusion of mycotoxins in feed that decreased IgA titers in both intestine and trachea. This information is important given that IgA is the isotype of immunoglobulin found in the mucosa, protecting at this level against antigens and toxins (54), and suggests that chicks receiving SDP in the diet have a greater immune capacity, as well as probably a stronger integrity of the gut barrier, as observed when chicks are subjected to systemic inflammation (55).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one of the organ systems that is most susceptible to heat stress is the gastrointestinal tract, as it decreases tight junction protein gene expression, leading to increased permeability and chronic systemic inflammation ( Tellez et al, 2017 ). Ruff et al (2021) worked with the supplementation of 2% SDP up to 28 d and 1% up to 42 d in the diet of birds subjected to heat stress and observed that the use of SDP reduced the negative effects of stress in birds raised in environments with high temperatures. In addition, it was reported that imposed continue heat stress improved BW and BWG for the 42-days period in broilers fed with SDP supplementation, which is consistent to what we observed in our second hatch under intermittent heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which broiler chicks were given bacitracin methylene disalicylate (BMD) antibiotic-or SDAP-supplemented (3%) diets and orally challenged with Salmonella Enteritidis (SE), it was reported that the SDAP diet mitigated the adverse effects of the SE challenge on broiler growth performance up to 2 weeks of age [123]. Furthermore, in high-temperature conditions (heat stress), partially feeding with SDAP helped mitigate adverse effects such as reduced body weight, feed intake, bone strength, increased feed conversion, and gut permeability [124].…”
Section: Spray-dried Animal Plasma In Poultry Nutritionmentioning
confidence: 99%
“…The measurement of fluorescein isothiocyanate dextran (FITC-d), a small molecule with a molecular size of 3-5 kDa that is normally not absorbed by the gastrointestinal tract, had been identified as a reliable biomarker for assessing gut permeability in poultry [129]. Studies have shown that the addition of SDAP to the diet of heat-stressed chickens reduced the serum concentrations of FITC-d, indicating an improvement in intestinal barrier function and gut integrity [124]. This reduction in FITC-d levels suggests a decrease in chronic systemic inflammation associated with increased gut permeability.…”
Section: Spray-dried Animal Plasma In Poultry Nutritionmentioning
confidence: 99%